A Critical Review of: “Ideology and Utopia: An Introduction to the Sociology of Knowledge, bBy Karl Mannheim”. - farhang ershad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Mannheim’s purpose in writing Ideology and Utopia: An Introduction to the Sociology of Knowledge was indeed to project the basic principles of sociology of knowledge. The fundamental question for him was about the problem of “how men think”. In his book, he argues the way of thinking by people, especially the intellectuals, in a socio-historical context within which the thoughts take place. So, his book has been the product of the critical historical duration, especially in the agitating time of Hungary and Germany during the years between the two world Wars and the time of Fascism power in Europe. He attempts to find the way of thinking and cognition, but he cannot emancipate from the conditions of thinking crisis in that time. However, he migrates from his home to Germany, and then to Britain under such unfavorable circumstances. Some readers emphasize that this Mannheim’s book is a philosophical work, while he believes that he has attempted to introduce the principles of thinking and knowledge and with his attention to the relation between thought and the socio-historical conditions (as relationism in Mannheim word), he feels that he is keeping distance from philosophy.